The Dynamic Role of Urban Neighborhood Effects in a Text-Messaging Adolescent Smoking Intervention - Mason, Michael J. (Nicotine Tob Res, 2016)
INTRODUCTION: Neighborhood features such as the density of tobacco outlets relative to one’s home and evaluations of safety of one’s activity space (routine locations), are known to influence health behaviors. Understanding the time-varying nature of these aspects of the urban ecology provides unique insights into the dynamic interactions of individuals and their environments. METHODS: The present study tested the time-varying effects of tobacco outlets and perceived safety within a randomized controlled trial of an adolescent text-messaging smoking intervention. We used ecological momentary assessment data (EMA) from an automated text-messaging smoking cessation randomized trial with 197 primarily African American urban adolescents. We employed a time-varying effect model to estimate the effects of density of tobacco outlets within one-half mile of participants’ home locations (time-invariant covariate) and evaluations of safety of their activity space (time-varying covariate) on momentary smoking over 6 months by treatment condition. The time-varying effect model approach models behavioral change and associations of coefficients expressed dynamically and graphically represented as smooth functions of time. RESULTS: Differences in trajectories of smoking between treatment conditions were apparent over the course of the study. During months 2 and 6, the association between tobacco outlet density and smoking was significantly stronger in the control condition, suggesting treatment dampens this association during these time periods. The intervention also significantly reduced the association of perceived safety and smoking among the treatment condition during months 3 through 6. CONCLUSIONS: Results support testing the time-varying effects of urban ecological features and perceptions of safety among adolescents in text-based smoking cessation interventions. IMPLICATIONS: This study makes a unique contribution towards understanding the time-varying effects of urban neighborhoods on adolescent tobacco use within the context of a text-delivered intervention. Helping to adjust the long-held conceptualization of intervention effects as a static outcome, to that of a dynamic, time-varying process, is an important contribution of this study. The ability to specify when behavioral change occurs within the context of a randomized control trial provides understanding into the time-varying treatment effects of text-based smoking intervention. For example, researchers can modify the intervention to have strategically timed booster sessions that align with when the odds of smoking begin to increase in order to provide more precise treatment. The current study results show that increasing support to participants during months 2 and 4 may help suppress smoking over the course of a 6-month intervention.